2007
DOI: 10.1097/mbp.0b013e32813fa371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin-converting enzyme gene polymorphism and serum vitamin D levels on ambulatory blood pressure measurement and left ventricular mass in Turkish hypertensive population

Abstract: The presence of the D allele is linked with a higher risk for left ventricular mass index in the Turkish hypertensive population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the third National Health and Nutrition Examination Survey (NHANES III), a large (n = 12,644) study representative of the US civilian population, there was a significant inverse correlation between systolic BP and pulse pressure with 25(OH)D3 levels [90]. Although similar findings were replicated by many investigators [105][106][107][108][109][110][111][112][113], this association was not confirmed by others, [81,[92][93][94][95][96][97][98] most of which, however, included fewer participants than NHANES III [92][93][94][95][96][97]. Overall, despite the inconsistent findings among cross sectional studies, the majority of those with large sample sizes demonstrated an inverse relationship between 25(OH)D3 levels and BP [116].…”
Section: Vitamin D and The Individual Components Of Mets Hypertensionmentioning
confidence: 77%
“…In the third National Health and Nutrition Examination Survey (NHANES III), a large (n = 12,644) study representative of the US civilian population, there was a significant inverse correlation between systolic BP and pulse pressure with 25(OH)D3 levels [90]. Although similar findings were replicated by many investigators [105][106][107][108][109][110][111][112][113], this association was not confirmed by others, [81,[92][93][94][95][96][97][98] most of which, however, included fewer participants than NHANES III [92][93][94][95][96][97]. Overall, despite the inconsistent findings among cross sectional studies, the majority of those with large sample sizes demonstrated an inverse relationship between 25(OH)D3 levels and BP [116].…”
Section: Vitamin D and The Individual Components Of Mets Hypertensionmentioning
confidence: 77%
“…Of interest, the ecological Intersalt Study, which examined more than 10 000 participants from around the world, showed that office BP was statistically significantly positively associated with distance from the equator, which was used as a proxy for ultraviolet B radiation exposure‐dependent vitamin D status [53, 54]. Most [8, 9, 11, 14, 17], but not all [15, 16], recent studies also found inverse correlations between 25(OH)D concentrations and office BP. Although Sweden is a country with limited sunlight during the winter, findings show that vitamin D insufficiency is rare in community‐dwelling elderly people [55].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies presented only correlations between plasma 25(OH)D concentration (which regulates the active compound 1,25‐dihydroxycholecalciferol (1,25(OH) 2 D) [7]) and office BP measurements [4, 8–16], with the exception of one study that used the more reliable measurement of 24‐h BP [17]. Analytical epidemiological studies investigating associations between 25(OH)D concentrations and hypertension status also used office BP measurements [18–29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the administration of ACE inhibitors in patients with the ACE DD genotype has been shown to decrease the level of calcitriol required (Pérez-Castrillón et al, 2006). In a hypertensive Turkish population, the presence of the ACE D allele, which correlates negatively with serum 25OHD levels, is linked to a higher left ventricular mass index value and elevated ambulatory blood pressure measurements (Kulah et al, 2007). In addition, genetic disruption of the VDR gene resulted in overstimulation of the RAS with increased renin and angiotensin II production, which lead to high blood pressure and cardiac hypertrophy.…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%